The history of political thought in national context (Cambridge University Press, 2001)
In this volume a distinguished international team of contributors characterises the nature of, and recent developments in, the history of political thought in their respective countries. The essays scrutinise not only the different academic histories and methodological traditions on which the study of the history of political thought has drawn, but also its relationship to cultural and political debates within nations. This collection represents a major contribution to the history of ideas, in which political thought has always been central, whilst reflecting the disciplinary tensions - and national differences - of what remains a 'borderline' subject, located at the intersection of history, politics and philosophy. The different national characteristics taken on by political discourse, and the complex relationship these characteristics have to the aspirations of the discipline itself, are considered in these wide-ranging essays, which cover the history of political thought in the UK, the USA, France, Germany, Italy, Central and Eastern Europe.